Penerapan penyusunan laporan keuangan pada Usaha Mikro Kecil Menengah berbasis Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) pada toko buk siti - Adawiyah, Putri; Wardayani, Wardayani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This journal research was conducted on one of the SMEs in Patumbak Village, namely Toko Buk Siti. This study aims to determine the utilization of financial detail readiness concerning preparing financial reports based on the Financial Accounting Standards for Micro, Small and Medium Entities at Toko Buk Siti. The research was conducted with a qualitative descriptive method. Based on the findings of this study, Buk Siti Shop business owners still need to gain a greater understanding of SAK EMKM. However, they can still make simple financial reports according to their knowledge. Recording financial statements by SAK EMKM has a positive effect on business. Because business owners now know that there are standards that are used as guidelines for making financial reports for the progress of a company that is being carried out.